A Review on Synthesis and Optoelectronic Applications of Nanostructured ZnO - Shahzad, Shazrah; Javed, Sofia; Usman, Muhammad (Frontiers in Materials, 2021)
Nanostructured ZnO has got a lot of interest as a suitable material for various applications especially sensing, energy conversion and storage. ZnO nanostructures can be synthesized in a number of ways. It is one of the materials that can be prepared in a variety of morphologies including hierarchical nanostructures. This review article presents a review of current research activities on growth of ZnO Nanorods. The article covers various water based routes of synthesis, and is further characterized by the type of substrate used for the growth. The growth factors involved in the hydrothermal and chemical bath deposition methods are discussed. These factors include the variety of precursors, time, temperature and the seeding method employed. At the end, applications such as gas sensing and improvement in opto-electric properties in relation to the morphology are discussed.